2019
DOI: 10.3390/app9081689
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Loading and Unloading Tests on Dry and Saturated Sandstone Specimens

Abstract: The brittle failure of hard rock due to the excavation unloading in deep rock engineering often causes serious problems in mining and tunneling engineering, and the failure process is always affected by groundwater. In order to investigate the effects of stress paths and water conditions on the mechanical properties and failure behavior of rocks, a series of triaxial compression tests were conducted on dry and saturated sandstones under various loading and unloading paths. It was found that when the sandstone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…In this line, Morrow et al [77] reported that the coefficients of friction dropped 20-60% with the addition of water for clay minerals which can take large amounts of interlayer water. Furthermore, these results are in agreement with the experimental data obtained by Li et al [78], who reported that both cpeak and ϕpeak values of saturated sandstones are lower than those of dry sandstones. Additionally, in other stone types, such as granites or meta-sedimentary rock materials, important decreases of ϕpeak due to water saturation have also been found [29], [76].…”
supporting
confidence: 93%
“…In this line, Morrow et al [77] reported that the coefficients of friction dropped 20-60% with the addition of water for clay minerals which can take large amounts of interlayer water. Furthermore, these results are in agreement with the experimental data obtained by Li et al [78], who reported that both cpeak and ϕpeak values of saturated sandstones are lower than those of dry sandstones. Additionally, in other stone types, such as granites or meta-sedimentary rock materials, important decreases of ϕpeak due to water saturation have also been found [29], [76].…”
supporting
confidence: 93%
“…Impact behavior is studied with reference to laminate composites [20,21]. Other papers devoted to rocks concern their cutting resistance [22] and their multiaxial response under dry and saturated conditions [23]. Finally, the mechanical behavior of a monomer structural component is studied in [24].…”
Section: Fracturementioning
confidence: 99%
“…The water weakening effect can be problematic for the stability of rock structures due to interactions between water and silicate minerals. Water weakens the hydrogen bonds, promotes the dissolution of clay minerals, and creates voids that can change the rock microstructure and ultimately weakens the rock [ 5 , 6 , 7 , 8 , 9 , 10 ]. In addition, pores inside a rock matrix act as flaws that create stress concentration and lead to macroscopic failure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The triaxial compressive strength of sandstone is affected by several factors, such as water content, confining stress, and porosity. Triaxial compression test results revealed a positive effect of confinement on compressive strength [ 1 , 7 , 18 , 19 , 20 ]. The influence of confining stress on the triaxial compressive strength of sandstone has been a subject of earlier investigations.…”
Section: Introductionmentioning
confidence: 99%